PENGARUH BOOK TAX DIFFERENCE DAN MANAJEMEN LABA TERHADAP PERTUMBUHAN LABA PERUSAHAAN - Kodriyah Kodriyah; Garnis artiwiya (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2016)
This study aims to determine the effect of book tax difference and Earning Management to profit growth. This study takes sample from pharmaceutical companylisted in the Indonesia Stock Exchange in 2010-2014. Were taked by purposive sampling that result 7 companies and method of analysis of this research used multi regression. The results showed that the book tax difference proxy for temporary difference not significantly affect profit growth, while earnings management significantly affect profit growth. simultaneously of book tax difference and earnings management had not influence to profit growth.  Keywords: Temporary difference, earnings management,  profit growth.